Kajian Teori dan Pandangan Alkitab Terhadap Kepemimpinan Otoriter - Adi Suhenra Sigiro; Friska Deniwaty Pasaribu; Destana Banurea; Ferdinan Majefat (PT. Giat Konseling Nusantara, 2026)
Authoritarian leadership is a leadership style that emphasizes full control and unilateral decision-making by the leader, without the involvement of subordinates. This article discusses theoretically the impact of authoritarian leadership on work motivation, organizational environment, and long-term productivity, using a literature study approach. Although this style is often viewed negatively because it reduces motivation, limits creativity, and creates a rigid work environment, authoritarian leadership also has benefits in certain contexts, such as in crisis situations, hierarchical organizational structures, and the need for high efficiency. This paper describes the characteristics, benefits, advantages, and disadvantages of authoritarian leadership, and emphasizes the importance of a balance between control and flexibility for organizational success. This study aims to provide critical insight into the application of authoritarian leadership style and its impact in the context of the world of work. When viewed from a biblical perspective, authoritarian leadership is very contrary to the Bible.